IMPROVEMENTS OF THE UNLOADING MECHANISM OF THE PYROLYSIS INSTALLATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article discusses the improved design of the unloading mechanism of the pyrolysis plant. With the help of pyrolysis plants, the process of upgrading low-grade coals of the southern region of Kyrgyzstan is carried out. In the known designs of the pyrolysis plant, the unloading of the finished product - semi-coke is carried out by tipping the pyrolysis plant manually, which is a laborious process. And if he manufactures a known design with a large capacity of up to one ton or more, a pyrolysis plant for putting into production, then a lifting mechanism is needed and at the same time the number of service personnel increases. The purpose of this article is the speed of removal of finished products from the pyrolysis plant, for which purpose an inclined self-dumping window for removing finished products is provided in the lower side of the pyrolysis plant. The removable window is installed on a fixed rail in the pyrolysis plant, and in order to unload the finished product, it is necessary to lift the self-draining window along the rail up, and the unloading process will take place. The resulting products of the proposed design of the new pyrolysis plant can be used in the heat and power industry of the Republic.
Keywords: pyrolysis plant, unloading mechanism, coal, semi-coke, guide.